Prototype Sistem Otomasi Jemuran Cerdas (Smart Clothesline) Berbasis NodeMCU ESP8266 dan Aplikasi Blynk - Pamungkas, Rully Panji Mustiko; Pristi, Anisa Nur; Hellyana, Corie Mei (TIN: Terapan Informatika Nusantara, 2025)
Indonesia experiences two seasons, the rainy season and the dry season, which often result in unpredictable weather and hinder household activities such as drying clothes. This study aims to design and construct an Internet of Things (IoT)-based automatic clothesline system capable of detecting weather conditions using an LDR (Light Dependent Resistor) sensor and a rain sensor, controlled via NodeMCU ESP8266. The system enables the clothesline to close automatically during rain or when sunlight intensity is insufficient. The research employs the prototype method, which involves the stages of design, development, testing, and evaluation. This study contributes to the development of logic that integrates rapid rain protection and light-based drying efficiency into a single system monitorable in real-time. Data were collected through observation, interviews, and literature review. Test results indicate that the device operates automatically based on weather conditions and can be remotely controlled using the Blynk application. Although the device has limitations, such as not closing at night in the absence of rain and limited manual control within the application, the system has proven effective in reducing user reliance on manual monitoring and offers a practical solution for modern IoT-based households.